Kejadian Demam Berdarah Dengue Di Kota Bandung Periode Tahun 2002-2006 - Roy Nusa Res (ASPIRATOR - Journal of Vector-borne Disease Studies, 2009)
Abstract. Kota Bandung is a big city located on an altitude between 675 meters above sea level in the south to 1050 meters above sea level in the north. These characteristics make this region is influenced by the humid and cool mountains climate with average temperature 23.1 °C. Based on data 2002 up to 2006, the case of DHF in this city is the highest in West Java Province. This paper describes the characteristics of intended DHF in Kota Bandung. Data are collected since 2002 to 2006 are processed to be presented in descriptive. From those periods of time, found that case’s weekly pattern are not always similar in every years, but there is a year that have case’s weekly pattern that relatively different from the other years.